2003
DOI: 10.1128/jcm.41.12.5598-5603.2003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Hepatitis B Virus X Protein (HBx) Antigen and Anti-HBx Antibodies in Cases of Human Hepatocellular Carcinoma

Abstract: Hepatitis B virus (HBV) infection can cause a wide spectrum of sequelae, ranging from asymptomatic chronic infection to chronic active hepatitis. Three hundred million people around the world are chronically infected with HBV (38, 39). Clinically, it is estimated that 5 to 10% of HBV-infected adults will develop chronic hepatitis (CH) and will thus be at a higher (Ͼ100 times) risk of developing hepatocellular carcinoma (HCC) (1,12,41). Several viral and host factors have been suggested to be involved in the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 42 publications
0
48
0
Order By: Relevance
“…It has been reported that HBx is preferentially maintained in HCC in the absence of other viral antigens [25] . However, the function of HBx in the transformation of human liver cells is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that HBx is preferentially maintained in HCC in the absence of other viral antigens [25] . However, the function of HBx in the transformation of human liver cells is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatocyte cell line L-O2 (Nanjing KeyGen Biotech Co Ltd, Nanjing, China), originating histologically from normal human liver tissue immortalized by stable transfection with the hTERT gene, has been used previously [21,[24][25][26][27] . L-O2-P (a cell line derived from L-O2 cells stably transfected with an empty pcDNA3 plasmid) and L-O2-X (a cell line derived from L-O2 cells stably transfected with the HBx gene) were established as described previously [28] .…”
Section: Cell Culturementioning
confidence: 99%
“…HBx is expressed at low levels during acute and chronic hepatitis and induces a humoral and cellular immune response (Chung et al, 1999;Hwang et al, 2002;Chun et al, 2003;Malmassari et al, 2005). In some studies, antiHBx antibodies were more frequent among patients with HCC than those with chronic hepatitis B without cancer (Hess et al, 1988;Levrero et al, 1991;Hwang et al, 2003). In most integrated subviral DNA, the HBx gene is maintained and transcribed and several studies have now demonstrated both HBx RNA and protein expression in human HCC tumor cells in the absence of HBV replication (Su et al, 1998;Peng et al, 2005).…”
Section: Hbxmentioning
confidence: 99%
“…Studies have found that patients with HCC produce HBx-specific antibodies with much greater frequency than patients with chronic HBV infection alone, with or without cirrhosis (70% vs. 5-15% respectively) [86][87][88] In addition, HBx RNA and protein can be demonstrated in HCC tissue samples. 81,86,87,89 Animal studies have provided evidence which implicates HBx in hepatocyte transformation and oncogenesis. Transgenic mice expressing HBx established by Koike et al frequently develop liver neoplasms (including HCC), particularly those demonstrating high levels of X gene product.…”
Section: Hepatitis B X Proteinmentioning
confidence: 99%